ECOMMERCE KEPADA PEDAGANG KAKI LIMA DAN UMKM KOTA PAYAKUMBUH UNTUK MENINGKATKAN DAYA SAING DI ERA GLOBAL - Winny Alna Marlina; Bintang Rizky Abdullah Majo Saibah; Ranny Fitriana Faisal; Agestayani Agestayani; Erizal Erizal; Susiana Susiana; Musbatiq Srivani (LPPM Universitas Andalas, 2018)
Payakumbuh is one of City on Sumatera Barat where having many street foods at night around 254 retailers. These food night retailers always move from another place to another place and lack of promotion. The purpose of our community service program is to enhance knowledge of street vendorts/retailers in Payakumbuh regarding technology especially e-commerce. The method of this is sharing and transferring knowledge and exercise. It was expected that participants will have a greater understanding in how to make the most of social media for business. The result of this public free service activity is kulinerpayakumbuh.com for helping promotion of the street food retailers in Payakumbuh. Based on our survey after this activity, the merchants were able to promote their products through the website, thus 41% participant could elevate their knowledge, and 13% participant could implement e-commerce to their business.